English For Technical Communication 2.0. UHL2422 - Chiam, Kee Swan; Mohammad Musab, Azmat Ali; Nor Ashikin, Abdul Aziz; Normala, Samsudin; Ruhil Amal, Azmuddin; Farah Liyana, Ahmad A’azmey (Penerbit UMP, 2017)
UHL2422 English for Technical Communication aspires to be a comprehensive Level II English course module for ESL learners undertaking degree programmes in Universiti Malaysia Pahang. The module covers an array of relevant technical communication topics for academic and professional purposes. The topics are categorised into four major units i.e. Technical Descriptions, Presentation